Long‐Term Crop Residue and Nitrogen Management Effects on Soil Profile Carbon and Nitrogen in Wheat–Fallow Systems. (1st November 2015) - Ghimire, Rajan; Machado, Stephen; Rhinhart, Karl
Abstract : Intensive cultivation of native grassland for dryland agriculture continuously depleted soil organic carbon (SOC) and nutrients. In 2010, we evaluated the influence of 80 yr of crop residue and nutrient management practices on SOC and N in 0‐ to 60‐cm soil depth profiles in conventionally tilled winter wheat ( Triticum aestivum L.)–summer fallow (WW–SF) system. Residue and N treatments, no N addition with fall burning (FB0), spring burning (SB0), and no burning (NB0), 45 kg N ha −1 with SB (SB45) and NB (NB45), 90 kg N ha −1 with SB (SB90) and NB (NB90), manure (MN, 5.32 Mg dry mass ha −1 yr −1 ), and pea vines (PV, 0.99 Mg dry mass ha −1 yr −1 ), were in ordered arrangement, and an undisturbed grassland (GP) was used as a reference. All WW–SF treatments had less SOC and N stocks than GP. The SOC stocks were lowest under FB0 with 50% less SOC than GP. The WW–SF treatments have depleted up to 63 and 26% of SOC and N from surface soil since 1931. Fall burning and MN treatments depleted SOC at rates of 0.64 and 0.17 Mg ha −1 yr −1 . Nitrogen stocks decreased at a rate of 0.02 Mg ha −1 yr −1 in FB, SB, and NB treatments, and 0.01 Mg ha −1 yr −1 in PV treatment. Reduction in tillage, application of low C/N ratio residues, and elimination of burning can improve sustainability of winter wheat production in the summer fallow region of the Pacific Northwest (PNW).